KEBIJAKAN PENGEMBANGAN KAWASAN EKONOMI KHUSUS (KEK) DI PROVINSI BANTEN - Alkadri, Alkadri (Jurnal Sains dan Teknologi Indonesia, 2011)
In recent years, the competitiveness of Banten Province in the national level tends to decrease. This is indicated by several macroeconomic indicators, i.e economic growth rate, share of investment, share of exports, unemployment rate and real income per capita. To enhance its competitiveness back, Banten Province will develop Special Economic Zones (SEZ). The area is chosen to be the location of SEZ is Bojonegara region. To make Bojonegara as SEZ, it must be pursued various policies, i.e the policy regarding the development of leading industries, the development of a competitive infrastructure, institutional formation of SEZ Bojonegara, human resource development and the promotion and dissemination. With the SEZ Bojonegara, expected some macroeconomic indicators above can be improved, which in turn can improve the competitiveness of Banten Province on the national and international level.